2010
DOI: 10.1246/cl.2010.493
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ordered Mesoporous α-Mn2O3 for Catalytic Decomposition of H2O2 at Low Temperatures

Abstract: Highly ordered mesoporous α-Mn2O3 with well-defined mesopores, high surface area, and high oxygen vacancy exhibits excellent catalytic activity toward H2O2 decomposition at low temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The mesoporous silica template (KIT-6) was synthesized following previously reported methods [26,[36][37][38][39][40]. A triblock copolymer (Pluronic P123, EO 20 PO 70 EO 20 , Aldrich) and tetraethylorthosilicate (TEOS, Aldrich) were utilized as the structure-directing agent and framework source, respectively.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…The mesoporous silica template (KIT-6) was synthesized following previously reported methods [26,[36][37][38][39][40]. A triblock copolymer (Pluronic P123, EO 20 PO 70 EO 20 , Aldrich) and tetraethylorthosilicate (TEOS, Aldrich) were utilized as the structure-directing agent and framework source, respectively.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…Reactions of H 2 O 2 with metal and metal oxide surfaces have been studied to some extent mainly due to their importance in areas ranging from catalysis to geo- and environmental chemistry and nuclear technology. Due to the complexity of the systems involved, which is dominated by the heterogeneity caused by the introduction of a solid phase, several mechanistic details remain to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity of hydrogen peroxide toward metal oxide surfaces has received increasing attention during the past decade. The main reason for this is the importance of such processes in nuclear technological installations . These studies have shown that hydrogen peroxide undergoes catalytic decomposition, primarily to form adsorbed hydroxyl radicals, on oxide surfaces of the type M x O y .…”
Section: Introductionmentioning
confidence: 99%